Shift of Bacterial Community in Synanthropic Mite Tyrophagus putrescentiae Induced by Fusarium Fungal Diet - Hubert, Jan (Public Library of Science, 2012)
BACKGROUND: Tyrophagus putrescentiae (Acari: Astigmata) and Fusarium sp. co-occur in poorly managed grain. In a laboratory experiment, mite grazing resulted in significant reduction of fungal mycelium on cultivation plates. The destruction of mycelium appeared to be a result of an interaction between the mites, fungi and associated bacteria. METHODOLOGY AND PRINCIPAL FINDINGS: A laboratory experiment was performed to simulate a situation of grain multiinfested by mites and Fusarium fungi. Changes of mite-associated bacterial community in T. putrescentiae were described in 3 habitats: (i) T. putrescentiae mites from a rearing diet prior to their transfer to fungal diet; (ii) fungal mycelium before mite introduction; (iii) mites after 7 day diet of each Fusarium avenaceum, F. culmorum, F. poae and F. verticillioides. Bacterial communities were characterized by 16 S rRNA gene sequencing. In total, 157 nearly full-length 16 S rRNA gene sequences from 9 samples representing selected habitats were analyzed. In the mites, the shift from rearing to fungal diet caused changes in mite associated bacterial community. A diverse bacterial community was associated with mites feeding on F. avenaceum, while feeding on the other three Fusarium spp. led to selection of a community dominated by Bacillaceae. CONCLUSIONS/SIGNIFICANCE: The work demonstrated changes of bacterial community associated with T. putrescentiae after shift to fungal diets suggesting selection for Bacillaceae species known as chitinase producers, which might participate in the fungal mycelium hydrolysis.